2023
DOI: 10.1101/2023.07.27.550914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The fate of bacterial secondary metabolites in the rhizosphere:Streptomycesdegrades and feeds on cyclic lipopeptides produced by competitors

Abstract: Cyclic lipopeptides are key bioactive secondary metabolites produced by some plant beneficial rhizobacteria such as Pseudomonas and Bacillus. They exhibit antimicrobial properties, promote induced systemic resistance in plants and support key developmental traits including motility, biofilm formation and root colonization. However, our knowledge about the fate of lipopeptides once released in the environment and especially upon contact with neighboring rhizobacteria remains limited. Here, we investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, a key outcome of such research to date is the finding that microbial degradation of LPs can result in structural changes that alter their biological activities. For example, in Bacillus , degradation of surfactin generates a linear surfactin which can no longer induce systemic resistance (ISR) in tobacco ( Rigolet et al, 2023 ). Linear surfactant also displays a reduced ability to lower surface tension when compared to cyclic surfactin ( Liu et al, 2015 ).…”
Section: Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a key outcome of such research to date is the finding that microbial degradation of LPs can result in structural changes that alter their biological activities. For example, in Bacillus , degradation of surfactin generates a linear surfactin which can no longer induce systemic resistance (ISR) in tobacco ( Rigolet et al, 2023 ). Linear surfactant also displays a reduced ability to lower surface tension when compared to cyclic surfactin ( Liu et al, 2015 ).…”
Section: Productionmentioning
confidence: 99%
“…More recently ( Hansen et al, 2023 ), reported the cooperative degradation of orfamide A by Rhodococcus globerulus D757 and Stenotrophomonas indicatrix D763 to protect orfamide-sensitive members of a synthetic community during co-culture with the orfamide-producer P. protegens . It has been proposed that degradation of CLPs could be a strategy deployed by competitors to prevent CLP producers from performing “critical” functions in their environment such as biofilm formation, enhancing motility or colonization of specific niches ( Rigolet et al, 2023 ). In another recent study ( Zhang et al, 2021 ), present a new role of LPs in mediating bacterial cooperation to evade amoebal predation.…”
Section: Productionmentioning
confidence: 99%
See 1 more Smart Citation